Effect of Different Adhesive Systems on Microleakage at the Amalgam/Composite Interface - F - Shirani; MR Malekipour; P Mirzakouchaki; P Zia (Isfahan University of Medical Sciences, 2006)
Introduction: Ditching and marginal defects of amalgam restorations can cause microleakage, recurrent carries, pulp hypersensitivity and finally loss of the tooth. The complete replacement of large restoration is time consuming, difficult and may potentially damage the pulp. Therefore in cases were there is no sings of recurrent caries, composite repair can be chosen as an alternative. The purpose of this study was to compare the effect of different bonding agent application on microleakage between flowable composite & amalgam.Methods and Materials: Standard calss V amalgam preparations were prepared on 60 carries free premolars and the cavities were filled using amalgam. After 24 hours, a 1 mm cavity on the occlusal margin of the class V restorations was prepared and specimens were divided randomly into four treatment groups: First group was filled with flowable composite and Single bond. Second group was filled with flowable composite and SE bond. Third group was filled with flowable composite and Prompt-L-pop. Fourth group Was filled with flowable composite without denting bonding agent. Specimens were thermocycled and sealed with fingernail polish except the composite-amlagam interface, then immersed in basic fuchsine for 24 hours. Specimens were sectioned and microleakage was assessed. The data were analyzed using Kruskal-Wallis test and Mann-Whitney U test.Results: The results indicated that dentin bonding agent is effective in decreasing the degree of microleakage in amalgam-flowable composite interface and also the clearfil SE bond was more effective than Prompt-L-pop. But there was no significant statistical difference in microleakage between SE bond and Single bond.Conclusion: The application of dentin bonding agents in repair of amalgam retoration using flowable composite decreases microleakage but more researches should be performed.Keywords: Amalgam repair, Microleakage, Dentin bonding agent, Flowable composite.